Assessment of the Public Procurement System in Republic of Bulgaria - World Bank (World Bank, Washington, DC, 2020)
Overall, commendable progress has been made in modernizing public procurement in Bulgaria since the procurement strategy was launched in 2014 and the landmark legislation was passed in 2016. This report provides an assessment of the public procurement system in Bulgaria, reviewing progress since the public procurement act was passed by Parliament in 2016, and providing a series of recommendations for further improvement. The government of Bulgaria should continue to co-ordinate relevant activities aimed at improving the public procurement system, including on the basis of the recommendations of this report.